Multisystem inflammatory syndrome in children associated with COVID-19: nursing care - Sofia Panato Ribeiro; Simone Boettcher (Hospital de Clínicas de Itajubá, 2021)
In 2019, a new viral disease, known as SARS-Cov-2 infection, was identified. Scientists believed that it was a disease with low morbidity for pediatric patients; however, a small percentage of children infected with the new coronavirus developed a multisystem inflammatory response, which aroused the interest of many researchers and health professionals. The objective of the study is to describe the main characteristics related to the Pediatric Multisystemic Inflammatory Syndrome Associated with Covid-19 (MIS-C), its complications and nursing care. The main clinical manifestations of MIS-C are hyperthermia, gastrointestinal symptoms, skin manifestations, generalized lymphadenopathy, cardiac and neurological disorders. The main nursing care was listed according to the signs and symptoms, such as monitoring of neurological and hydroelectrolytic changes. The nurse professional must add knowledge about MIS-C so that he is able to qualify his care and improve his skills to provide quality care to pediatric patients.